2019
DOI: 10.5144/0256-4947.2019.155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and 20-year epidemiological trends of glomerular diseases in the adult Saudi population: a multicenter study

Abstract: BACKGROUND: Recent international reports have shown significant changes in the incidence of different glomerular diseases.OBJECTIVE: Examine temporal and demographic trends of biopsy-diagnosed glomerular diseases in the adult population of Saudi Arabia over the last two decades.DESIGN: Medical record review.SETTINGS: Four tertiary medical centers in Saudi Arabia.PATIENTS AND METHODS: We identified all patients that underwent native kidney biopsy between 1998 and 2017.MAIN OUTCOME MEASURES: The frequency and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In South America, a Brazilian study found focal segmental glomerulosclerosis to be the most frequent aetiology (28.8%) and only 18.3% were IgA nephropathy [24]. Finally, epidemiological studies in the Middle East reported that focal segmental glomerulosclerosis was the most commonly diagnosed glomerulonephritis (35% of cases) in Iraq, whereas IgA nephropathy accounted for only 7% of cases [25] and in Saudi Arabia focal segmental glomerulosclerosis accounted for 39.8% of cases [26].…”
Section: Discussionmentioning
confidence: 98%
“…In South America, a Brazilian study found focal segmental glomerulosclerosis to be the most frequent aetiology (28.8%) and only 18.3% were IgA nephropathy [24]. Finally, epidemiological studies in the Middle East reported that focal segmental glomerulosclerosis was the most commonly diagnosed glomerulonephritis (35% of cases) in Iraq, whereas IgA nephropathy accounted for only 7% of cases [25] and in Saudi Arabia focal segmental glomerulosclerosis accounted for 39.8% of cases [26].…”
Section: Discussionmentioning
confidence: 98%
“…14 In contrast to a previous 20-year-long study, we found a higher prevalence of FSGS in the pediatric population in our study. 15 The multicenter study from Saudi Arabia reported that among the several glomerulonephrites, FSGS was most frequent, with an average prevalence of 21.2 in the last 20 years. 15 In a similar study by Mubarak et al mean age of 9.79±4.59 years was reported, which WAS greater than the current study.…”
Section: Discussionmentioning
confidence: 99%
“…15 The multicenter study from Saudi Arabia reported that among the several glomerulonephrites, FSGS was most frequent, with an average prevalence of 21.2 in the last 20 years. 15 In a similar study by Mubarak et al mean age of 9.79±4.59 years was reported, which WAS greater than the current study. A much higher occurrence of minimal change disease, i.e., 43.8, was observed compared to the 12.32 occurrence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the sequale of diabetes mellitus that occur after long time is the progressive development of the some complications like retinopathy with possibility of development of blindness, nephropathy with possibility of development of renal failure, and/or neuropathy (4). A recent study conducted by AlFaadhel et al in Saudi Arabia (5). They found that the most common secondary types of glomerular diseases was the systemic lupus erythematosus-associated lupus nephritis followed by diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 97%